Identification of Physics Concepts in the Local Wisdom of Remo Surabaya Traditional Dance as One of the Efforts to Preserve Culture in East Java - Irgy Redityo Dawana; Afaurina Indriana Safitri; Setyo Admoko (STKIP Singkawang, 2023)
Indonesia has a variety of cultures that can be used for ethnoscience-based learning. Indonesian culture will be better known if it is integrated into education, one of which is physics learning. One of the cultures that exist in Indonesia is the Remo Dance which is a traditional dance originating from East Java. Dance is a cultural heritage that we need to preserve because culture is a reflection of a nation. This research was conducted with the aim of identifying the physics concepts contained in the Remo Gagrak Anyar Dance so that they can be integrated into physics learning activities. This study uses a qualitative descriptive method with observations, interviews, and a literature study. Based on the results obtained, there are physics concepts in Remo Dance, including the material of muscle force, Newton's third law, gravity, circular motion, static balance, sound sources, and light. The results of this study indicate that there is potential in ethnoscience-based physics teaching materials and can be applied to physics learning to help students improve understanding and learning outcomes. Other local cultural studies can be carried out to facilitate contextual understanding of the material in various subjects and aim to preserve the culture of the Indonesian nation.